Nonword Repetition and Speech Motor Control in Children. - Reuterskiöld, Christina; Grigos, Maria I. (BioMed Research International, 2015)
This study examined how familiarity of word structures influenced articulatory control in children and adolescents during repetition of real words (RWs) and nonwords (NWs). A passive reflective marker system was used to track articulator movement. Measures of accuracy were obtained during repetition of RWs and NWs, and kinematic analysis of movement duration and variability was conducted. Participants showed greater consonant and vowel accuracy during RW than NW repetition. Jaw movement duration was longer in NWs compared to RWs across age groups, and younger children produced utterances with longer jaw movement duration compared to older children. Jaw movement variability was consistently greater during repetition of NWs than RWs in both groups of participants. The results indicate that increases in phonological short-term memory demands affect articulator movement. This effect is most pronounced in younger children. A range of skills may develop during childhood, which supports NW repetition skills.